The impact of home confinement by COVID-19 on mood state and adaptive behaviors in Spanish swimmers - Jose Carlos Jaenes; David Alarcon Rubio; María José Arenilla-Villalba; Dominika Wilczynska (Akademia Wychowania Fizycznego i Sportu w Gdansku, 2023)
Introduction: This study aimed to assess the mental condition of aquatic athletes during COVID-19 lockdowns and identify factors that could predict changes in their emotions and mood disturbances. Materials and Methods: The sample was composed of 506 competitive swimmers (ages 15-36) in four aquatic specializations, with 82.4% competing at the national level. Data was collected through questionnaires between April 10th and May 1st, 2020. Results: Female athletes had higher levels of unpleasant mood states and were generally more vulnerable to the lockdown's harmful effects. Team athletes had higher levels of friendliness, which may be a coping strategy for difficult situations. Training conditions played a significant role in mental health, with athletes who trained more having fewer mood disturbances. Lack of training negatively impacted fitness and mental health. Conclusions: The study emphasizes the importance of providing support to athletes during pandemics and reducing stigmatization around seeking psychological support.